PERUBAHAN TARIF PADA PP 23 TAHUN 2018, SANKSI PERPAJAKAN DAN TINGKAT PEMAHAMAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM - Hunein, Hamida; Aprianti, Ahyani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
The purpose of this study was to analyze the effect of the independent variable Tariff Changes in PP 23 of 2018, Tax Sanctions and the Understanding of Taxes. The dependent variable is UMKM Taxpayer Compliance in the Tigaraksa-Tangerang warehouse market. This research is quantitative descriptive.The sampling method used is the Purposive Sampling method with a total sample used with 193 respondents. The analysis technique used is multiple linear regression analysis using the Statistical Product and Service Solution (SPSS.25) program for windows.The results of this study: Variable Rates Decline in PP 23 of 2018 Against UMKM Taxpayer Compliance has a significant effect, Tax Sanctions on UMKM taxpayer compliance have no significant effect, The level of Tax Understanding of UMKM taxpayer compliance has a significant effect. Variable Changes to Tariffs in PP 23 of 2018, Tax Sanctions and the Level of Understanding of Tax simultaneously affect the UMKM Taxpayer Compliance